PERANCANGAN PLTS ATAP ON GRID SYSTEM PADA KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH PENELITIAN DAN PENGEMBANGAN KOTA PROBOLINGGO - Ardiansyah, Allan; Setiawan, I Nyoman; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
The rooftop on-grid PLTS system is commonly used by people from the household, commercial, to industrial sectors to reduce electricity bills from PLN. Based on PERMEN ESDM 49 of 2018, the export value of electrical energy to the PLN electricity grid is 65%, and if energy exports are greater than energy bills, the rest will be stored and accumulated in the following month. This is only valid for a maximum of 3 months, in the 4th month the remaining energy export savings will be eliminated. Determining the right PLTS capacity makes the contribution of PLTS in making bill savings more optimal. The office of BAPPEDA LITBANG Probolinggo City was used as the research location. The PLTS Scenario 1 design uses a capacity according to the energy needs of the office, which is 21.6 kWp, and the PLTS Scenario 2 capacity is greater than the office energy requirement of 32.4 kWp. Based on the investment feasibility analysis using the NPV, PI, and DPP methods, it shows that the Scenario 1 and Scenario 2 PLTS designs are feasible to run. PLTS Scenario 1 and Scenario 2 investment is Rp. 267,000,000 and Rp. 395.85 million, respectively. The benefit of saving bills for 30 years of PLTS operation, in Scenario 1 is Rp. 406,863,069 or 152% of the total investment, while Scenario 2 is Rp. 595,619,904 or 150% of the total investment.